Traumatic injuries of the duodenum - Ríos Bruno, Guaymirán; Ibarburu, Sergio (Cirugía del Uruguay, 1975)
Eighteen cases of traumatic injuries of the. duodenum are discussed. They correspond to a 13-year period in the Emergency Department of the Hospital de Clínicas. This report shows that these lesions have evidently increased in the last few years, due to factors which are considered in the discussion. It is remarked how exceptionally pancreatic association was present in this series ( 1 case: 5 % ) . Preoperative diagnosis is difficult, due to severa! circumstances mentioned; it was never done in the cases under consideration. Tbe mechanism, anatomo-clinical types and the therapy used in each case are discussed, insisting upan the severity of the associated lesions and upan the need of a correct surgical exploration .of the abdomen. In 16 cases, a simple closing of the lesion was performed. Evolution was satisfactory in the same percentage of cases. Seventy-two per cent of the patients underw ent post-operative complications: 27 % of them required anuther surgery. Two patients (11 % ) died: one due to puJmonary embolism and another because of associated lesions. In both cases the duodenal suture, controllec by necropsy, was in good condition.